Prevalence of Sinew String in patients coming to a tertiary care hospital of Nepal: A descriptive cross-sectional study - Shrestha, P; Shrestha, K; Acharya, L; Shakya, S (Journal of Nepalese Prosthodontic Society, 2020)
Introduction: Sinew strings are frenum or wrinkle like entity of mandibular distal buccal mucosa which is frequently encountered in the population. Sinew strings play an important role in determining the width and buccal extension of the denture flange of mandibular complete denture. Materials and Methods: This descriptive cross-sectional study was conducted at a tertiary care hospital from 17th June 2020 to 20th September 2020. Convenient sampling (n=245) was done. Point estimate at 95% Confidence Interval was calculated along with frequency and proportion for binary data. Data analysis was done in Statistical Package for the Social Sciences version 21. Results: Among the study population (n=245 participants), sinew string was seen in 35% of the participants. The frequency of sinew string present bilaterally was 19% while it was present unilaterally in 16% of the population. Conclusions: The presence of sinew string in the sampled Nepalese population showed a higher prevalence than previous studies.